Alternative security solutions offered by virtual private network vpn model proposal to use alternatives to Cisco and Microsoft security in al-rasheed bank-delegate general office- northern region - الدباغ, رائد عبد القادر; زينل, بشرى علي (Journal of Economics and Administrative Sciences, 2018)
The study aims to provide a Suggested model for the application of Virtual Private Network is a tool that used to protect the transmitted data through the Web-based information system, and the research included using case study methodology in order to collect the data about the research area ( Al-Rasheed Bank) by using Visio to design and draw the diagrams of the suggested models and adopting the data that have been collected by the interviews with the bank's employees, and the research used the modulation of data in order to find solutions for the research's problem.The importance of the study Lies in dealing with one of the vital topics at the moment, namely, how to make the information transmitted via information systems celebrating safety, which is missed by many organizations, despite its importance, and providing the means for the protection and safety of the information transmitted from the center to the branches and back again to the center.In order to achieve the goals of the study, we build the suggested model, by using the  Virtual Private Network through Cisco and Microsoft suggested models, The study concludes a set of conclusions, the most important, adopt a proposed model to use Virtual Private Network, whether the model presented by Cisco or through the application form provided by Microsoft.In light of the findings, the study concluded a set of including, adopting the model of Microsoft Virtual Private Network due to the easy to apply using the infrastructure of the bank as tubeless to special equipment.